Hypertension in the eastern province of Saudi Arabia: Results of a screening campaign - Khalid A Al-Turki; Nadira A Al-Baghli; Aqeel J Al-Ghamdi; Ahmad G El-Zubaier (Wolters Kluwer Medknow Publications, 2008)
Objective: To estimate the prevalence of hypertension through a screening campaign in the Eastern Province of Saudi Arabia, and examine its association with lifestyle factors. Research Design and Methods: In 2004, all Saudi residents in the Eastern Province, aged 30 years and above were invited to participate in a screening campaign for the early detection of diabetes and hypertension. Blood pressure was recorded by trained nurses using a mercury sphygmomanometer, based on the recommendations of (JNC- VII). A positive screening test for hypertension was defined as systolic and/or diastolic blood pressure of ≥ 140 and 90 mm Hg, respectively. Subjects who had positive screening tests were asked to come on the following day for a confirmation of the reading. Hypertension was considered if there was a persistent reading of systolic and/or diastolic blood pressure of > 140 and 90 mmHg after confirmation, or when there was history of a previous diagnosis. Results: 21% of the sample was positive from previous history or screening. After confirmation, the prevalence of hypertension dropped to 15.6%, pre-hypertension was 3.7%, whereas the prevalence of undiagnosed hypertension was 2.8%. The prevalence rose with age. It was higher in women than in men of all age groups and in all sectors of the eastern province, although the mean systolic and diastolic BP was higher in men than women. It was higher with lower education, in widows and divorcees than others (P<0.0001). Conclusion: The yield of the screening for abnormal blood pressure was high. Systematic follow-up of subjects with abnormal screening results is vital.